A collaborative model in persuasive web design: multiple case study of Lazada and Shopee - Loh, Yin Xia; Choon Sen Seah, Choon Sen Seah; Muhammad Arif, Ezatul Emilia; Jalaludin, Farah Waheeda; Chin, Wai Yin; Abdul Hamid, Nor Aziati (2023)
This study examined online persuasion through website design by using the Elaboration Likelihood Model (ELM) and Persuasive System Design (PSD). This study investigates the phenomenon of the success of Lazada and Shopee to provide guidelines for website designers and local sellers to enhance the e-commerce website’s persuasiveness. The persuasive design features in Lazada’s and Shopee’s e-commerce websites were evaluated based on the design criteria of the ELM and the PSD model. This study has examined (1) the influence of central route elements (Dialogue Support and Primary Task Support) towards Lazada and Shopee user’s attitude change, (2) the influence of Lazada and Shopee user’s attitude change towards behavioral intention and (3) the influence of Lazada and Shopee user’s behavioral intention towards actual online buying behavior. A total of 414 samples were analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM) technique. The results from the analysis indicated that Primary task support through navigation design (PTN) was found to be the most influential persuasive design criteria, followed by Social support through connectedness (SSC), and Dialogue support through argument quality (DSA).